Expanding the molecular spectrum of tenosynovial giant cell tumors - Gauduchon, Thibault; Vanacker, Helene; Pissaloux, Daniel; Cassier, Philippe; Dufresne, Armelle; Karanian, Marie; Meurgey, Alexandra; Bouhamama, Amine; Gouin, François; Ray-Coquard, Isabelle; Blay, Jean-Yves; Tirode, Franck; et al. (Frontiers in Oncology, 2022)
Background While the clinical and pathological description of tenosynovial giant cell tumors (TCGT) is relatively well known, the molecular heterogeneity of this disease is increasingly described. Indeed, some cases lack the canonical oncogenic fusions CSF1::COL6A3, suggesting other oncogenic mechanisms. The aim of this study was to explore by RNA sequencing a retrospective series of tumors diagnosed as TCGT, in order to provide a better description of their molecular landscape and to correlate it to the clinical data. Methods We analyzed clinicopathological and performed whole-exome RNA sequencing on 41 TCGT samples. Results RNAseq analysis showed significant higher CSF1 and CSF1-R expression than a control panel of 2642 solid tumors. RNA sequencing revealed fusion transcripts in 14 patients with 6 of them not involving CSF1, and some of which are previously unreported. Unsupervised clustering on the expression profiles from this series indicated that tumors could be gather in two distinct subgroups: one composed of various molecular subtypes including CSF1 and FN1 rearranged samples and one composed of four tumors with an HMGA2::NCOR2 fusion, suggesting a distinct tumor entity. Overall, 15 patients received at least one systemic anti-CSF1R treatment with clinical improvement in 11 patients (including patients from both clusters). Discussion This study confirms the molecular heterogeneity of TGCT, contrasting with the clinical and pathological homogeneity and the ubiquitous high level of expression of CSF1 and CSF1R. The impact of this molecular diversity on the efficacy of systemic treatments needs to be further investigated.